A randomised controlled trial in preterm infants comparing prophylactic with selective “less invasive surfactant administration” (pro.LISA) - Wolfgang Göpel; Tanja K. Rausch; Barbara Mitschdörfer; Silke Mader; Egbert Herting; Inke R. König; Guido Stichtenoth; on behalf of the pro.LISA study group (Trials, 2023)
Abstract Background Respiratory distress syndrome is the main cause of mortality and morbidity in preterm infants. “Less invasive surfactant administration” (LISA), which describes intratracheal surfactant administration to spontaneously breathing infants via a small diameter tube, is recommended as the first-line treatment in preterm infants with more than 30% supplemental oxygen. Prophylactic use of LISA in preterm infants with less than 30% supplemental oxygen was not tested in randomised controlled trials yet, and long-term outcome data of the procedure are scarce. Methods Preterm infants with a gestational age between 25 weeks + 0 days and 28 weeks + 6 days who are breathing spontaneously on continuous positive airway pressure with supplemental oxygen at or below 30% in the first hour of life will be randomised to a prophylactic LISA treatment with 100–200 mg surfactant intratracheally per kilogramme bodyweight (intervention group) or will continue the continuous positive airway pressure treatment (control group). Participants will have follow-up until age 5 years. At that time, the children will be tested by spirometry, and forced expiratory volume within 1-s z-scores will be compared between the intervention and control groups as the primary outcome parameter of the trial. Secondary endpoints include additional lung function parameters, endurance, motor development, intelligence, and sensitivity for infectious lung diseases. Short-term safety assessment will be done after completed enrolment (n = 698) and discharge of all infants. This safety assessment will include in-hospital mortality and short-term complications. Discussion Robust data concerning the possible long-term benefits of prophylactic LISA treatment are lacking. The current observational data from the German Neonatal Network indicate that approximately 50% of preterm infants with supplemental oxygen at or below 30% within the first hour of life are treated with LISA. The pro.LISA trial will provide short- and long-term outcomes of preterm infants receiving prophylactic treatment and will clarify if prophylactic treatment should be given to all preterm infants or if the current practice of selective treatment if supplemental oxygen exceeds 30% is more appropriate. Trial registration German Clinical Trials Register DRKS00028086. Prospectively registered on 8 February 2022.